Predicting the exchange rate path: The importance of using up-to-date observations in the forecasts - Håvard Hungnes (Statistics Norway, Research Department, 2020)
Central banks, private banks, statistical agencies and international organizations such as the IMF and OECD typically use information about the exchange rate some weeks before the publication date as the basis for their exchange rate forecasts. In this paper, we test if forecasts can be made more accurate by utilizing information about exchange rate movements closer to the publication date. To this end, we apply new tests for equal predictability and encompassing for path forecasts. We find that the date when the exchange rate forecast is based on is crucial and this finding should be taken into account when evaluating exchange rate forecasts. Using forecasts made by Statistics Norway over the period 2001 - 2016 we find that the random walk, when based on the exchange rate three days ahead of the publication date, encompassed the predicted path by Statistics Norway. However, when using the exchange rate two weeks before the publication deadline, which is the information used by Statistics Norway in practice when making their forecasts, the random walk path and the predicted exchange rate path by Statistics Norway have equal predictability.
Keywords: C53; F31; 330; Macroeconomic forecasts; Econometric models; Forecast performance; Forecast evaluation; Forecast comparison